Examining the Relationship Between Home and School Computer Use and Students’ English/Language Arts Test Scores - O'Dwyer, Laura; Russell, Michael; Bebell, Damian; Tucker-Seeley, Kevon R. (The Journal of Technology, Learning and Assessment, 2005)
With increased emphasis on test-based accountability measures has come increased interest in examining the impact of technology use on students’ academic performance. However, few empirical investigations exist that address this issue. This paper (1) examines previous research on the relationship between student achievement and technology use, (2) discusses the methodological and psychometric issues that arise when investigating such issues, and (3) presents a multilevel regression analysis of the relationship between a variety of student and teacher technology uses and fourth grade test scores on the Massachusetts Comprehensive Assessment System (MCAS) English/Language Arts test. In total, 986 fourth grade students from 55 intact classrooms in nine school districts in Massachusetts were included in this study. This study found that, while controlling for both prior achievement and socioeconomic status, students who reported greater frequency of technology use at school to edit papers were likely to have higher total English/language arts test scores and higher writing scores. Use of technology at school to prepare presentations was associated with lower English/language arts outcome measures. Teachers' use of technology for a variety of purposes were not significant predictors of student achievement, and students’ recreational use of technology at home was negatively associated with the learning outcomes.